DISCOVERY LEARNING BERBASIS GOOGLE EARTH SEBAGAI INOVASI PEMBELAJARAN KONDISI GEOGRAFIS INDONESIA UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS VI - Varavita, Gusti Ayu; Fitra Raharja, Hawwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Google Earth based Discovery Learning model on sixth-grade elementary school students’ understanding of the concept of Indonesia’s geographic conditions. The background of this research is based on the fact that geography learning is still predominantly theoretical and provides limited contextual learning experiences, causing students to often have difficulty understanding abstract concepts. The use of Google Earth in the Discovery Learning model is expected to present geographic objects and phenomena visually, interactively, and engagingly, thereby improving students’ conceptual understanding. The research method used was a quantitative approach with a quasi-experimental design of the pretest–posttest control group type. The research instrument was a concept understanding test that had been validated by experts. The data were analyzed using tests of normality, homogeneity, and a t-test. The results of the independent samples t-test analysis showed a significance value (2-tailed) of < 0.001, indicating a significant difference between the experimental class and the control class. The average improvement in conceptual understanding of students in the experimental class reached 73.55%, which was higher than that of the control class. Therefore, it can be concluded that the implementation of Google Earth–based Discovery Learning is effective as a geographical learning innovation to improve elementary school students’ conceptual understanding.